The Java programming language - Arnold, Ken, 1958- 4 0 16; Gosling, James; 5 (Reading, MA : Addison-Wesley, 1998)
A guide to Java programming for people who are familiar with basic programming techniques, focusing on the Java 1.1 edition, covering the core features of Java, the program's error-handling capabilities, the built-in language and runtime support for String objects, multithreading, packages, and other topics.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Java (Computer program language). -- 20; 20; 2